Metropolitan Museum of Art: Two Bowls with Fish Motifs
Two bowls installed in Metropolitan Museum of Art's Islamic Art galleries. Shows influence of Chinese material culture on Islamic culture: specifically, the impact of imported Southern Song porcelain on Ilkhanid stonepaste ceramic production.